2014
DOI: 10.1073/pnas.1420906112
|View full text |Cite
|
Sign up to set email alerts
|

Subunit determination of the conductance of hair-cell mechanotransducer channels

Abstract: Cochlear hair cells convert sound stimuli into electrical signals by gating of mechanically sensitive ion channels in their stereociliary (hair) bundle. The molecular identity of this ion channel is still unclear, but its properties are modulated by accessory proteins. Two such proteins are transmembrane channel-like protein isoform 1 (TMC1) and tetraspan membrane protein of hair cell stereocilia (TMHS, also known as lipoma HMGIC fusion partner-like 5, LHFPL5), both thought to be integral components of the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
199
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(211 citation statements)
references
References 39 publications
12
199
0
Order By: Relevance
“…In apical OHCs, both are cation channels that pass Ca 2+ with P Ca /P Cs = ∼5.8 in normal and ∼1.5 for reverse-polarity channels; both are blocked by external FM1-43 with IC 50 of ∼3 μM in normal and 26 μM in unconventional channels; the unitary conductances are similar in apical OHCs, with values in 1.5 mM Ca 2+ of 63 pS in normal and 61 pS for unconventional channels. However, in basal OHCs the normal channels are about twofold larger than the reverse-polarity channels, a difference that depends on the presence of TMC1, which may contribute to an external vestibule (9,31). In both cases the channels are blocked by extracellular Ca 2+ , lowering its concentration to a few tens of micromolars, increasing channel conductance by 50%.…”
Section: Discussionmentioning
confidence: 98%
“…In apical OHCs, both are cation channels that pass Ca 2+ with P Ca /P Cs = ∼5.8 in normal and ∼1.5 for reverse-polarity channels; both are blocked by external FM1-43 with IC 50 of ∼3 μM in normal and 26 μM in unconventional channels; the unitary conductances are similar in apical OHCs, with values in 1.5 mM Ca 2+ of 63 pS in normal and 61 pS for unconventional channels. However, in basal OHCs the normal channels are about twofold larger than the reverse-polarity channels, a difference that depends on the presence of TMC1, which may contribute to an external vestibule (9,31). In both cases the channels are blocked by extracellular Ca 2+ , lowering its concentration to a few tens of micromolars, increasing channel conductance by 50%.…”
Section: Discussionmentioning
confidence: 98%
“…Yeast two-hybrid and coimmunoprecipitation experiments have shown that the CD1 and CD3 isoforms of protocadherin-15 interact directly with Tmc1 and Tmie (Maeda et al 2014). All three isoforms of protocadherin-15 were found to coimmunoprecipitate with both TMC1 and TMC2 (Beurg et al 2015). In another study, Zhao and colleagues showed that the CD2 isoform bound Tmie directly, but that the CD1 and CD3 isoforms bound Tmie only indirectly, via Tmhs see Fig.…”
Section: Constructing the Tip-link Interactomementioning
confidence: 96%
“…These four proteins are Tmc1 (transmembrane channel protein 1), Tmc2 (transmembrane channel protein 2) (Beurg et al, 2014(Beurg et al, , 2015Kawashima et al, 2011;Pan et al, 2013), Tmhs (tetraspan membrane protein of hair cell stereocilia, also know as Lhfpl5) (Beurg et al, 2015;Longo-Guess et al, 2007, 2005Xiong et al, 2012) and Tmie (transmembrane protein of inner ear hair cells) (Karuppasamy et al, 2012;Mitchem et al, 2002;Park et al, 2013; Su CD3-specific sequence (encoded by exon 39) is indicated in yellow, and the sequence encoded by exon 37 is indicated in green. Protein sequences encoded by phases other than the conventional phase are indicated in gray.…”
Section: Q4mentioning
confidence: 99%